ИМПОРТОЗАМЕЩЕНИЕ КАК ФАКТОР ИНТЕГРАЦИИ ПРОМЫШЛЕННОСТИ РОССИИ В СЕГМЕНТЫ ГЛОБАЛЬНОГО РЫНКА - Nizharadze, S. (EurasianUnionScientists, 2020)
The article is devoted to the analysis of such a concept as import substitution. In particular, the authors considered possible strategies for implementing import substitution in Russia at the present stage, and analyzed the structure of imports.